Self-Perceived Stress During the Quarantine of COVID-19 Pandemic in Paraguay: An Exploratory Survey - Torales, Julio; Ríos-González, Carlos; Barrios, Iván; O'Higgins, Marcelo; González, Israel; García, Oscar; Castaldelli-Maia, João Mauricio; Ventriglio, Antonio (Frontiers in Psychiatry, 2020)
Introduction: Any viral pandemic is a global health and mental health issue. The World Health Organization and mental health associations have warned that the current COVID-19 pandemic will lead to a drastic increase of stress-related conditions and mental health issues globally. Materials and methods: An online web-based survey has been launched from 10 to 15 April 2020 in Paraguay in order to collect information regarding the stress related to the quarantine during the COVID-19 pandemic. It has been spread through social media ("WhatsApp", "Twitter", and "Facebook"). 2206 Paraguayan citizens, over 18 years of age, completed the survey voluntarily. Socio-demographics as well as ratings at Self-perceived Stress Scale have been collected and analyzed. Results: 2206 subjects (74.12% men) aged between 18 and 75 with an average of 34±11 years old completed the survey. 12.42% (276 subjects) of sample reported a preexisting diagnosis of mental disorder, and 175 participants (7.93%) reported an increase of preexisting symptoms with the onset of COVID-19 quarantine. 41.97% of them had anxiety and 54.38% did not receive any specific treatment. The general population rated 18.10 ±5.99 at Self-perceived Stress Scale, which indicates a moderate level of self-perceived stress. Significant association was found between higher levels of stress and female sex, being single or reporting preexisting mental disorder, above all anxiety and depression (p<0.01). In fact, in 63.87% of mentally ill subjects (n=175), the quarantine has worsened symptoms of preexisting mental disorders. Conclusion: This study suggests a stressful impact of COVID-19 pandemic, with the majority of participants reporting a moderate level of self-perceived stress. We suggest mental health services to provide a phone-based or web-based support to the general population in order to contrast the psychological impact of the pandemic. This approach may improve the accessibility to mental healthcare services in Paraguay, especially in times of social distancing.